Dissecting the Binding Interactions of Teixobactin with the Bacterial Cell‐Wall Precursor Lipid II. (12th November 2019) - Chiorean, Sorina; Antwi, Isaac; Carney, Daniel W.; Kotsogianni, Ioli; Giltrap, Andrew M.; Alexander, Francesca M.; Cochrane, Stephen A.; Payne, Richard J.; Martin, Nathaniel I.; Henninot, Antoine; Vederas, John C.
Abstract: The prevalence of life‐threatening, drug‐resistant microbial infections has challenged researchers to consider alternatives to currently available antibiotics. Teixobactin is a recently discovered "resistance‐proof" antimicrobial peptide that targets the bacterial cell wall precursor lipid II. In doing so, teixobactin exhibits potent antimicrobial activity against a wide range of Gram‐positive organisms. Herein we demonstrate that teixobactin and several structural analogues are capable of binding lipid II from both Gram‐positive and Gram‐negative bacteria. Furthermore, we show that when combined with known outer membrane‐disrupting peptides, teixobactin is active against Gram‐negative organisms. Abstract : Mighty macrocycles : an in‐depth look at the binding parameters of teixobactin, a macrocyclic antimicrobial peptide, with its membrane target, lipid II. Teixobactin binds to analogues of both Gram‐positive and Gram‐negative bacterial lipids, allowing its activity scope to be extended to both types of organisms using membrane‐disrupting peptides.